Indicators of The Development of Enterprises from the SME Sector in the Conditions of COVID-19 Pandemic in Poland - Lukasz BRZEZINSKI; Magdalena Krystyna WYRWICKA (Communications of International Proceedings, 2020)
The Development Of Small And Medium-Sized Enterprises (Smes) Is An Important Subject Of Interest In The Field Of Economic And Social Sciences. It Is Caused, Inter Alia, By The Influence Of The SME Sector Entities On The Socio-Economic Processes Taking Place In The Modern Economy. In Many Countries, Small And Medium-Sized Enterprises Constitute An Important Base Of Entrepreneurship And Create A Dynamically Developing Sector Of The Economy, But On The Other Hand, It Is An Extremely ”Delicate” Sphere Of Activity, Susceptible To The Influence Of Various Factors And Conditions. In This Aspect, The COVID-19 Pandemic – Caused By The SARS-Cov2 Coronavirus – Can Be Indicated. It Started As An Epidemic On November 17th 2019 In Wuhan, Hubei Province, Central China, And On March 11th 2020, Was Declared A Pandemic By The World Health Organization (WHO) (Coronavirus…, 2020). The Health Crisis Caused By COVID-19 And The Ongoing Isolation Of Many Markets Pose Unprecedented Challenges To People And Economies Around The World. According To The International Labour Organization, About 2.7 Billion Workers (81% Of The World’s Workforce) Are Partially Or Completely Cut Back On Work. In The Second Quarter Of 2020, Up To 195 Million People Could Lose Their Jobs, Including 12 Million People In Europe Alone. To Mitigate The Effects Of The Crisis, Governments Of Many Countries Are Introducing Various Support Programs For Entrepreneurs And Employees (Pulshra…, 2020). In Order To Overcome The Economic Slowdown, Organizations Should Adapt To The New Reality, Which On The One Hand May Generate Barriers, But Also Development Factors. The Article Will Present The Results Of An Expert Survey On Barriers And Factors For The Development Of Small And Medium-Sized Enterprises During The COVID-19 Pandemic In Poland. The Aim Of The Article Is To Identify Potential Barriers And Determinants Of The Development Of Economic Entities From The SME Sector In Poland During The COVID-19 Pandemic, Based On The Opinions Of Experts.
Keywords: Enterprise Development; COVID-19 Pandemic; Sector of Small and Medium Enterprises; Determinants of Enterprise Development; Barriers of Enterprise Development.